EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERN PENERIMAAN DAN PENGELUARAN KAS PADA PT. DYNACAST INDONESIA TAHUN 2014 - Yovita Susanti; Firdaus Hamta (EQUILIBIRIA, 2014)
This study aimed to examine the effect of the application of the accounting information system of internal control cash receipts and disbursements PT. Dynacast Indonesia. In this study, researchers attributed the accounting information system and internal control were used and owned the company in cash receipts and disbursements  Population and sample in this research is employees at PT. Dynacast Indonesia. By using the technique of purposive sampling techniques. Method of research done by triangulation of data sources.  Results of this study, namely the application of accounting information system and internal control cash receipts and payments on PT. Dynacast Indonesia obtained the conclusion that in the application of accounting information system is good and in the internal control, there are still shortcomings, namely the absence of the serial number on the form and the two functions performed by one person so that monitoring the flow of documentation and internal control of cash poor.